Instructional Leadership and the Adoption of Contextual Digital Teaching Materials in Madrasah: Implications for Indonesian Language Writing Instruction - Reni Octaviani; Haryadi; Mai Syaroh; Zahid Zufar At Thaariq (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2026)
Madrasah leaders face growing pressure to make decisions about digital learning resources, yet limited evidence guides how those decisions should support language instruction. This study examines the role of contextual digital teaching materials in Indonesian language writing instruction, framed as a problem of instructional leadership and resource decision-making in Islamic schools. The authors conducted a systematic literature review of articles published between 2015 and 2024, drawing from Scopus-indexed and Indonesian-accredited sources. After screening against eligibility criteria, fifteen sources were retained for thematic synthesis through reduction, classification, and pattern identification. The synthesis indicates that contextual digital teaching materials yield stronger writing outcomes than purely informative digital materials in three areas: idea development, textual organization, and critical thinking. Effects extend to learner motivation and self-regulated learning, but their realization depends on teacher digital competence, infrastructure, and curricular alignment with Islamic educational values. Without intentional integration of authentic and culturally grounded contexts, digital materials reinforce technical writing features without deepening content quality. The findings suggest that adoption decisions in madrasah settings function as instructional leadership acts linking resource selection to teacher capacity development and pedagogical philosophy, rather than technical procurement choices. The article recommends that madrasah leaders treat contextual digital teaching material adoption as a coupled decision involving curriculum design, human resource management, and infrastructure planning, supported by sustained professional development. Future empirical work should test the proposed framework through field studies in Islamic school settings.